From overtourism to undertourism, and back again - Cairns, D.; Clemente, M. (The immobility turn: Mobility, migration and the covid-19 pandemic, 2023)
In this chapter, we explore the impact of the COVID-19 pandemic on the tourism industry in Portugal, using findings from fieldwork conducted during 2021 and 2022. The aim is to learn more about the challenges industry stakeholders have faced during an unprecedented and unpredictable public health emergency. In Chapter 1, we noted the extent of the financial losses incurred during the first two years of the pandemic, and in Chapter 2, some of the moral quandaries that arose out of attempts to keep travelling during times of restricted circulation. We now wish to take a more in-depth look at these issues.